Sistem Asesmen Kompetensi dalam Penetapan Kelulusan SMA Negeri 2 Salatiga (Studi Perspektif Guru Sebagai Agen Pembelajaran) - Yohana Adventria Narsinta; Bambang Ismanto; Lelahester Rina (Jurnal Paedagogy, 2022)
This research aims to analyze teachers’ perspectives as learning agents on the competency assessment system in graduation determination in SMA Negeri 2 Salatiga. The national assessment includes socialization, practice, teachers’ perspectives, and control. At the same time, an assessment provides literacy, numeration, and character assessment. The researcher took the data by qualitative methodology in this study, consisting of interviews, observations, and documentation. This research had the subject of the principal of SMA Negeri 2 Salatiga, the vice principal of curriculum, and the teacher. This study used interactive model data analysis techniques to check the validity of source triangulation data. The result showed that SMA Negeri 2 Salatiga had been assessed for graduation determination. The teachers understood the purpose of the assessment, although there are several pros and contra to implementation, such as some teachers have complained about several complex assessments. It caused teachers to need a long time for students’ character assessments. Then, most teachers assumed that assessment for graduation determination was appropriate for students because it made students think more critically. Also, it would improve the education field because a national exam is considered not a flexible assessment.